2018
DOI: 10.11604/pamj.2018.29.171.12392
|View full text |Cite
|
Sign up to set email alerts
|

Tumeur pancréatique rare de découverte fortuite chez un enfant en Côte d’Ivoire

Abstract: La tumeur pseudo-papillaire et solide du pancréas (TPPSP) est une tumeur rare. Elle touche le plus souvent la femme jeune. Décrite la première fois par Frantz en 1959, sa pathogénie demeure peu claire. C’est une tumeur de bon pronostic qui nécessite une chirurgie radicale. Les auteurs rapportent un cas de TPPSP chez une fillette de 11 ans. La symptomatologie était aiguë, faite de syndrome de compression et d’épigastralgies. L’examen trouvait une masse solide de l’hypochondre gauche. Le scanner montrait une mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…According to the topography, the tumor was corporal-caudal in our case, which is identical to the case reported by Richard Azagoh-Kouadio et al in Ivory Coast [7]. In their series of 553 Chinese cases, Peng-Fei Yu et al [10] found that the most frequent site was the head of the pancreas (39.8%), followed by the tail (24.1%), body and tail (19.5%), and the body of the pancreas (11.2%) [8].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…According to the topography, the tumor was corporal-caudal in our case, which is identical to the case reported by Richard Azagoh-Kouadio et al in Ivory Coast [7]. In their series of 553 Chinese cases, Peng-Fei Yu et al [10] found that the most frequent site was the head of the pancreas (39.8%), followed by the tail (24.1%), body and tail (19.5%), and the body of the pancreas (11.2%) [8].…”
Section: Discussionsupporting
confidence: 90%
“…Tumor cells also sometimes express neuroendocrine markers [10] [12]. Our patient and those of Nabil Jakhlal [6], Richard Azagoh-Kouadio [7], and Arzu Neşe Yener [8] underwent corporo-caudal pancreatectomy removing the tumor. The only curative treatment for SPT is surgery.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations